Designing research funding schemes to promote global health equity: An exploration of current practice in health systems research. Issue 2 (23rd November 2016) - Pratt, Bridget; Hyder, Adnan A.
Abstract: International research is an essential means of reducing health disparities between and within countries and should do so as a matter of global justice. Research funders from high‐income countries have an obligation of justice to support health research in low and middle‐income countries (LMICs) that furthers such objectives. This paper investigates how their current funding schemes are designed to incentivise health systems research in LMICs that promotes health equity. Semi‐structured in‐depth interviews were performed with 16 grants officers working for 11 funders and organisations that support health systems research: the Alliance for Health Policy and Systems Research, Comic Relief, Doris Duke Foundation, European Commission, International Development Research Centre, Norwegian Agency for Development Cooperation, Research Council of Norway, Rockefeller Foundation, UK Department of International Development, UK Medical Research Council, and Wellcome Trust. Thematic analysis of the data demonstrates their funding schemes promote health systems research with (up to) five key features that advance health equity: being conducted with worst‐off populations, focusing on research topics that advance equitable health systems, having LMIC ownership of the research agenda, strengthening LMIC research capacity, and having an impact on health disparities. The different types of incentives that encouraged proposed projects to have these features are identified and classified by their strength (strong, moderate, weak). It is suggested that research funders ought to create and maintain funding schemes with strong incentives for the features identified above in order to more effectively help reduce global health disparities.